Energy Conservation and the Promotion of Legionella pneumophila Growth: The Probable Role of Heat Exchangers in a Nosocomial Outbreak. (19th September 2016) - Bédard, Emilie; Lévesque, Simon; Martin, Philippe; Pinsonneault, Linda; Paranjape, Kiran; Lalancette, Cindy; Dolcé, Charles-Éric; Villion, Manuela; Valiquette, Louis; Faucher, Sébastien P.; Prévost, Michèle
Abstract : OBJECTIVE: To determine the source of a Legionella pneumophila serogroup 5 nosocomial outbreak and the role of the heat exchanger installed on the hot water system within the previous year. SETTING: A 400-bed tertiary care university hospital in Sherbrooke, Canada. METHODS: Hot water samples were collected and cultured for L. pneumophila from 25 taps (baths and sinks) within wing A and 9 taps in wing B. Biofilm (5) and 2 L water samples (3) were collected within the heat exchangers for L. pneumophila culture and detection of protists. Sequence-based typing was performed on strain DNA extracts and pulsed-field gel electrophoresis patterns were analyzed. RESULTS: Following 2 cases of hospital-acquired legionellosis, the hot water system investigation revealed a large proportion of L. pneumophila serogroup 5 positive taps (22/25 in wing A and 5/9 in wing B). High positivity was also detected in the heat exchanger of wing A in water samples (3/3) and swabs from the heat exchanger (4/5). The outbreak genotyping investigation identified the hot water system as the source of infections. Genotyping results revealed that all isolated environmental strains harbored the same related pulsed-field gel electrophoresis pattern and sequence-based type. CONCLUSIONS: Two cases of hospital-acquired legionellosis occurred in the year following the installation of a heat exchanger to preheat hospital hot water. No cases were reported previously, although the same L. pneumophila strain was isolated from the hot water system in 1995. The heat exchanger promoted L. pneumophila growth and may have contributed to confirmed clinical cases. Infect. Control Hosp. Epidemiol. 2016;1475–1480